Exploring A1 activation and miR-155 modulation in ALS spinal cord astrocytes - Sequeira, Catarina Antunes (2021)
Amyotrophic Lateral Sclerosis (ALS) is a neurodegenerative disorder, characterized by motor neurons (MN) loss in the brain and spinal cord (SC). Astrocyte reactivity and microglia activation account for neurodegeneration through the release of neurotoxins. Cytokines from activated microglia were shown to activate astrocytes and the inhibition of microglial microRNA(miRNA)-155 in ALS mice with G93A mutation in SOD1 gene (mSOD1) to recover their steady state phenotype and to attenuate disease progression. This thesis explored the reactive/inflammatory signature of ALS SC mSOD1 astrocytes, their response to microglial cytokines and the efficacy of anti-miR-155 modulation in recovering astrocyte neuroprotective properties. Astrocytes were isolated from the SC of 8-day-old mSOD1 mice pups and after 11 days in vitro, cells were incubated with cytokines that mimic A1-microglial activation (IL-1α/TNF-α/C1q) during 48h. Mutated astrocytes were transfected (or not) with anti-miRNA-155 and their secretome added to mSOD1-NSC-34 MN-like cells for 48h. We demonstrated that mSOD1 astrocytes have an inflammatory profile (elevated miR-21, miR-124, miR-155, IL-1β, Cx43 and HMGB1), further upregulated by A1-stimulation. Though a similar elevation of miR-155, iNOS and TNF-α was observed in both WT and mutated cells upon stimulation, increased levels of miR-21, miR-124, Cx43 and IL-6 mRNA, together with GFAP, S100B and vimentin protein were more evident in mSOD1 astrocytes, while IL-1β and IL-10 mRNAs remained unchanged and lower miR-146a upregulation was found. Downregulation of miR-155 in mSOD1 astrocytes reduced IL-1β, TNF-α and HMGB1, while upregulated IL-6, IL-10, SOCS1 and miR-146a. Importantly, secretome from astrocytes transfected with anti-miR-155 increased cell survival, mitochondria viability and neurite number in degenerating mSOD1-NSC-34 MN-like cells, in part mediated by miR-124 downregulation. Our results highlight the inflammatory/reactive/aberrant phenotype of mSOD1 SC astrocytes and its exacerbation by activated microglia as players in ALS neuroinflammation. Importantly, treatment with anti-miR-155 reduces the pro-inflammatory pattern of ALS astrocytes and restores their neuroprotective properties.